Implementasi Problem Based Learning Berbasis E-LKPD Interaktif Untuk Meningkatkan Kemampuan Komunikasi Peserta didik - Rike Widya Lestari; Fahdian Rahmandani (Jurnal Studi Guru dan Pembelajaran, 2023)
This article discusses the selection of interactive E-LKPD based Problem Based Learning in the learning process as a form of learning that becomes students in the 21st century. This research was carried out in line with student development and curriculum renewal in Indonesia. The application of Interactive E-LKPD based Problem Based Learning to students in this study aims to improve students' communication competence, especially in Pancasila Education subjects. The methodology used is classroom action research. Data acquisition was obtained by observation techniques and teacher's diary notes. This study uses inductive data analysis techniques. The results obtained for three cycles in this study were based on Problem Based Learning based on Interactive E-LKPD which was effective for increasing students' communication competence. The findings faced by researchers in the implementation of interactive E-LKPD-based Problem Based Learning are that researchers must divide study groups evenly according to the number of students, gender and ability level of students, and monitor each group on a regular basis to determine the stage of development of students.